IMPLEMENTASI REGULASI PENYIARAN PROGRAM BERITA KAREBA TERKINI DI SINJAI TV (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
Crime news in the mass media always attracts people's attention, especially news about crimes, such as murder, theft, robbery, or rape. This can be seen from the many news programs that specifically present criminal news. However, in its development, this news program has drawn criticism from television observers because it is considered too vulgar and can have a negative impact on society. To reduce the negative impact that can arise from criminal broadcasts, media practitioners must be guided by broadcasting regulations. Broadcasting Law No. 32 of 2002 then mandated the formation of the Indonesian Broadcasting Commission (KPI) whose task was to formulate guidelines and standards for broadcasting programs and oversee broadcasts in Indonesia. From the explanation above, questions arise: How is the implementation of broadcasting regulations in the latest Kareba news program? The theory used in this research is Mike Feintuck's theory which contains three components which include broadcasting regulation, namely structural regulation containing media ownership by the market, behavioral regulation intended to regulate the management of property used in relation to competitors, and content regulation containing restrictions on broadcast material. what can and can't be broadcast. The approach used in this research is a qualitative approach. The qualitative approach aims to explain the phenomenon in depth through the collection of data as deeply as possible. Through interviews and observations, it can be seen whether the KAREBA TERKINI news program has implemented the broadcasting regulations of Law no. 32 of 2002 on article 48 paragraph 4 point d (restrictions on sex scenes, violence and sadism) or not. , and sadism). This can be seen from the broadcast of KAREBA TERKINI October 12, 2021-21 October 2021, there is 6 news related to the article. 6 news including Kareba Terkini has implemented broadcasting regulations. The implementation of broadcasting regulations in the latest Kareba program is by disguising victims of rape or immoral acts, disguising victims of tragic accidents, not explicitly presenting violence, visualizing accidents and murders with animation. Broadcasting No. 32 of 2002 and also to protect the human rights of victims.